Physicochemical characteristics and nutritional compositions of MR219 mutant rice and their effects on glycaemic responses in BALB/c mice - Kadar, Asma Ilyani; Yusop, Mohd Rafii; Hussein, Sobri; Ling, Anna Pick Kiong; Harun, Abdul Rahim; Tengku Muda Mohamed, Mahmud; Sakimin, Siti Zaharah; Ramli, Asfaliza; Abisola, Oladosu Yusuff (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2019)
The awareness of the general public on healthy foods has been a major concern and people are looking for the right variety of rice for diabetic patients. High amylose content rice with low glycaemic index (GI), which is an indicator of sugar release in the blood, is beneficial for human health. The present work was aimed to determine the physicochemical characteristics and nutritional compositions of MR219 mutant rice, and the effects of amylose content to blood glucose response and glycaemic index in field condition. A total of 31 M4 mutant lines (ML1 to ML31) were evaluated for physicochemical characteristics and nutritional compositions in comparison with the parental variety, MR219. In glycaemic response study, 48 female BALB/c mice were fed with glucose (a baseline), saline water, two check varieties (MR219 and MRQ74) and four selected mutant lines with different amylose contents. The physicochemical and proximate analysis revealed highly significant differences among the mutant lines. Some mutant lines improved amylose content and nutritional composition. Mutant ML3 had slightly higher amylose content than the parental variety and was recommended for glycaemic responses. However, the field experiment results showed two mutant lines namely; ML3 and ML30, having significantly lower glucose reading (5.49 mmol/L and 5.47 mmol/L, respectively) as compared to the parental variety and other mutant lines. The glucose level was found highest at 60 min after feeding but significantly dropped at 120 min. The normal glucose reading in ML3 and ML30 also resulted in moderate GI values (65% and 66%, respectively). As low and moderate GI foods are recommended for diabetic patients, ML3 and ML30 had high potential for their consumption, and can be suggested for further breeding program to develop low GI rice.